Antibiotics administration during last trimester of pregnancy is associated with atopic dermatitis - a cross-sectional study - Panduru Mihaela; Epure Adina Mihaela; Cimpoca Brindusa; Cozma Cristina; Giuca Brigitta Ana; Pop Andrei; Pop Gabriel; Simon Larisa Georgiana; Robu Mircea; Panduru Nicolae Mircea (Sciendo, 2020)
Introduction. Studies regarding antibiotics administration during pregnancy and atopic dermatitis (AD) in children are only few. In this context, the objective of our study was to investigate the potential association between the timing of intrauterine exposure to antibiotics or prenatal antibiotic administration in general and AD occurrence in children.